2019
DOI: 10.1002/slct.201803255
|View full text |Cite
|
Sign up to set email alerts
|

High Photosensitized Singlet Oxygen Generating Zinc and Chloroindium Phthalocyanines Bearing (4‐isopropylbenzyl)oxy Groups as Potential Agents for Photophysicochemical Applications

Abstract: In this study, novel phthalonitrile derivatives (1 and 2) and their peripherally and non‐peripherally tetra (4‐isopropylbenzyl)oxy‐substituted zinc and chloroindium phthalocyanine complexes (3‐6) have been prepared for the first time. The synthesized phthalonitrile derivatives and phthalocyanine complexes were characterized spectroscopically. Not only the chloroindium phthalocyanines but also zinc phthalocyanines are essentially free from aggregation in THF at the studied micromolar concentration. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…All compounds carrying chloro indium ( 1b , 2b , 3b and 4b ) as the central atom have higher singlet oxygen efficiency than the zinc derivatives ( 1a , 2a , 3a and 4a ) due to the heavy atom effects of larger indium (Table 1). Besides, the complexes 1a and 1b have higher photochemical effects than their respective references (unsubstituted ZnPc (Φ Δ = 0.67) (39) and unsubstituted ClInPc (Φ Δ = 0.61) (48). When comparing 3a and 4b , we observed that the position effect competes with the metal effect.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…All compounds carrying chloro indium ( 1b , 2b , 3b and 4b ) as the central atom have higher singlet oxygen efficiency than the zinc derivatives ( 1a , 2a , 3a and 4a ) due to the heavy atom effects of larger indium (Table 1). Besides, the complexes 1a and 1b have higher photochemical effects than their respective references (unsubstituted ZnPc (Φ Δ = 0.67) (39) and unsubstituted ClInPc (Φ Δ = 0.61) (48). When comparing 3a and 4b , we observed that the position effect competes with the metal effect.…”
Section: Resultsmentioning
confidence: 90%
“…The photophysicochemical features of all the stated macromolecules were examined according to the methods described in Refs. (35–39). The related methods and equations have been extensively explained in the "" section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both complexes exhibited sluggish photodegradation kinetics as judged from the unchanged UV-visible spectra in DMSO solution even after irradiation for 40 min. This suggested that the ground-state complex or triplet oxygen might not attack the excited state of the ruthenium-phthalocyanine complexes under irradiation at 660 nm, as opposed to what is generally observed for phthalocyanine derivative complexes (Idowu and Nyokong, 2009;Demirbaş et al, 2019;Güzel et al, 2019). Molecular orbital mixing between phthalocyanine and Ru(II) or (III) might have stabilized the phthalocyanine cycle due to the high activation energy process involving attack by singlet oxygen.…”
Section: Discussionmentioning
confidence: 91%
“…Singlet oxygen quantum yield was measured in dimethylformamide (DMF) solution under aerobic conditions. It was performed according to a previously described method [42][43][44][45][46]. 1,3-Diphenylisobenzofuran (DPBF) was applied as a singlet oxygen chemical quencher.…”
Section: Measurement Of Singlet Oxygen Quantum Yieldmentioning
confidence: 99%